Preparation process of matting wax powder

By modifying silica in situ in the water system and adding wax powder, the problem of limited amount of wax powder and complex process in the prior art is solved, efficient extinction and scratch resistance are achieved, the process is simplified and environmentally friendly performance is improved.

CN119875421APending Publication Date: 2025-04-25HENAN UNIVERSITY +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510098253.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, the amount of wax powder used in silica matting agent is limited, making it difficult to achieve both matting performance, scratch resistance and smooth feel at the same time. At the same time, the process is complex and involves a large number of organic solvents, which affects environmental protection.

Method used

Silica is prepared by precipitation method and modified in situ in the water system. Wax powder is added to prepare matte wax powder, avoiding the use of organic solvents, simplifying the process, and high proportional addition is achieved by regulating the ratio of silica to wax powder.

Benefits of technology

It achieves the improvement of scratch resistance and wear resistance of the coating film while ensuring the extinction effect, simplifies the process, avoids the use of organic solvents, and significantly improves the environmental performance of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a preparation process of matting wax powder, which is characterized in that wax powder and silicon dioxide are compounded in the synthesis process of modified nano silicon dioxide to obtain the matting wax powder. The surface property of silicon dioxide is regulated and controlled, so that the silicon dioxide has strong organophilic property, and the wax powder and the silicon dioxide are tightly combined; and the wax powder and the silicon dioxide play a synergistic effect of extinction and scratch resistance by adjusting the interface bonding mode of the wax powder and the silicon dioxide. The matting wax powder can be used in oily and water-based coatings, and not only can obtain excellent matting performance when being used for coating films on the surfaces of base materials such as leather, wood and metal, but also can greatly improve the hardness and scratch resistance of the surfaces of the films. According to the invention, an environment-friendly method is adopted for preparation in a water system, and no organic solvent is involved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coating application, and in particular relates to a preparation process of wax powder-modified silicon dioxide matting wax powder, which can be used in oily and water-based coating systems. Background Art

[0002] Silica is widely used as a matting agent because of its high specific surface area, large pore volume, and refractive index close to that of resin coatings. PE wax powder, as a kind of organic matting agent, can not only provide certain matting properties, but also give the coating certain wear resistance, water resistance and anti-fouling properties, and a smooth feel. However, since there are almost no polar groups in the PE wax molecules, the hydrophilicity is poor, and the addition has a great impact on the transparency of the coating, the wax powder can only be added in a small amount at present, and it is difficult to meet the application requirements in many scenarios. At present, some companies use a small amount of PE wax to heat above the melting point or dissolve it in an organic solvent to prepare matting powder by coating the surface of nano-silica, which can effectively improve the dispersibility of nano-silica. However, after the PE wax is melted or dissolved, the molecular chain will enter the pores of nano-silica, reducing its pore volume, resulting in a significant decrease in matting performance after the addition amount is increased. Therefore, the general amount of wax in the silica matting agent is not more than 20%.

[0003] The method of modifying silica with wax powder mostly involves adding wax powder to an organic solvent to allow the molten / dissolved wax to enter the pores of silica. This process usually involves organic solvents, which imposes a heavy burden on the environment. Alternatively, the surface of silica powder particles is coated with wax powder to obtain wax-coated silica particles. The coating structure limits the amount of wax powder added, and usually only a small amount can be coated on the surface of silica, which cannot simultaneously take into account the anti-scratch function of the wax powder and the matte performance of silica.

[0004] CN 113382804 A discloses porous silica treated with one or more waxes, wherein the wax is dissolved in an organic solvent, the silica particles are mixed with the wax solution, the wax having fluidity is coated on the surface of the silica particles, and the pores of the porous silica are partially filled, and then the organic solvent is removed and the porous silica is cooled and ground. The organic solvent includes toluene. The patent involves a large amount of organic solvents, which is not environmentally friendly, and the obtained particles need to go through multiple steps of grinding, screening, and crushing, and the process is relatively complicated.

[0005] CN 111471344B discloses a silicon dioxide matting powder and a preparation method thereof, wherein silicon dioxide and an organic alcohol are first mixed, the pH is adjusted, and the mixture is reacted for a period of time to obtain a mixed solution, and a silane coupling agent and PE wax are added to the mixed solution to obtain blended silicon dioxide and wax powder. The organic solvent includes ethanol, ethylene glycol, n-butanol, etc. The amount of wax powder added is low, and the weight ratio of wax powder to silicon dioxide is 1:30.

[0006] CN 103467829 B discloses a wax aqueous dispersion loaded with nano-silicon dioxide, wherein silicon dioxide prepared by a sol-gel method is synthesized and concentrated in an ethanol / water system, polyethylene wax micropowder dispersed in ethanol is added, and a vinyl-containing silane coupling agent is added under the action of a promoter and ground for more than 2 hours, so that silicon dioxide is coated on the surface of the wax powder to form a core-shell structure. The patent uses a large amount of organic solvent ethanol, and the ratio of silicon dioxide to wax in the obtained dispersion is between 1:10 and 1:8, which has good friction resistance, but the coating has poor gloss extinction effect.

[0007] Based on the above-mentioned defects in the prior art, this application was developed. Summary of the invention

[0008] The present invention aims to overcome the defects of the prior art and provide an environmentally friendly matting wax powder preparation process for the problems existing in the current matting products themselves and in the use process, so as to ensure a good matting effect while making the coating film have certain scratch resistance, wear resistance and smooth feel. The method is simple in process, green and environmentally friendly, and can be used in oily and water-based coating systems.

[0009] To achieve the above object, the present invention adopts the following technical solution: A process for preparing matte wax powder comprises the following steps: S1: Adjust the pH value of a certain concentration of sodium silicate solution to 3-10, and react at 40-95°C for 0.5-10h to synthesize silica slurry; S2: adding a modifier to the synthesized silica slurry, reacting at 40-95° C. for 1-6 hours to prepare an in-situ modified silica slurry; S3: After the reaction is completed and a certain temperature is reached, wax powder is added to the in-situ modified silica slurry, and the mixture is stirred and emulsified to obtain a silica composite wax powder suspension; S4: drying the suspension to prepare a composite powder; S5: crushing the composite powder to obtain a low-gloss matte wax powder product.

[0010] Specifically, the modulus of the sodium silicate solution used in step S1 to synthesize the silica slurry can be 2.3-3.6, and the silica content can be 20-30%. The concentration of the silica slurry synthesized in step S1 is 4%-18%, Furthermore, in step S1, the pH can be adjusted by adding one or more of an inorganic acid such as sulfuric acid, hydrochloric acid, nitric acid, an organic acid such as citric acid, acetic acid, oxalic acid, and sodium bicarbonate, ammonium bicarbonate, etc.

[0011] Specifically, the modifier used in step S2 can be one or more of silane coupling agent, polysiloxane, cationic surfactant, nonionic surfactant, etc., and the amount of the modifier accounts for 3% to 40% of the solid content in the silica slurry. The silane coupling agent includes silane coupling agents containing saturated alkyl, vinyl, epoxy, amino, etc. The in-situ synthesized and modified silica slurry in S2 is a water system and does not contain an organic solvent.

[0012] Specifically, the wax powder in step S3 can be one or more of polyethylene wax powder, polypropylene wax powder, polytetrafluoroethylene wax powder, hydrophilic wax powder, oxidized wax powder, wax emulsions of different melting points, etc.; the amount of wax powder added accounts for 10% to 50% of the solid content of the silica slurry in S2. Further, the temperature in step S3 is 20 to 80°C, the stirring emulsification time is 0.5 to 4 hours, and the stirring speed is 300 to 1000 r / min.

[0013] Specifically, the drying in step S4 can be one of centrifugal spray drying, pressure spray drying, flash drying and fluidized bed drying, etc., and the pulverization in step S5 can be mechanical pulverization or air flow pulverization, etc.

[0014] The present invention also provides a low-gloss matte wax powder product prepared by the above process. The median particle size of the final product is 3-25 microns and the wax content is 9-33%.

[0015] The present invention also provides a method for using the above-mentioned matte wax powder, which mixes the matte wax powder and polyurethane or polyacrylate in a high-speed mixer, mixes at a speed of 1500r / min for 5min until the coating is evenly mixed, and uses a 9# wire rod to apply film on a PU leather substrate, with a wet film thickness of 20.5μm. After the film is applied, the sample is placed in a blast drying oven at 100°C for 35s, taken out and cooled to room temperature, and a multi-angle gloss meter is used for gloss test. 18# wire rod is used to apply film on black cardboard simulating a wood base, with a wet film thickness of 41.1μm, and after natural drying for 24h, a multi-angle gloss meter is used for gloss test. The matte wax powder and acrylic amino baking varnish are mixed in a high-speed mixer to prepare the coating, and an 18# wire rod is used to apply film on a tinplate sheet simulating a metal surface, and the film is placed at room temperature for 5 min until the surface is dry, and then transferred to a 140°C blast drying oven for drying for 30min, and its pencil hardness is tested, which can intuitively express the scratch resistance of the coating surface.

[0016] The present invention adopts a precipitation method to prepare silicon dioxide, adds sodium carbonate and pure water to a reactor in a certain proportion, slowly drips sulfuric acid therein after reaching a certain temperature, adds a silane coupling agent to the reactor when silicon dioxide particles are initially generated, and performs in-situ modification on the silicon dioxide particles, which can effectively improve the agglomeration phenomenon of silicon dioxide particles caused by dehydration condensation of silanol groups. At the same time, its compatibility with organic solvents is further improved, and wax powder is added to the modified silicon dioxide suspension to prepare a matte wax powder. In the synthesis process of modified nano-silicon dioxide, the present invention composites wax powder with silicon dioxide to obtain a matte wax powder, reduces the surface polarity of silicon dioxide by an organic modifier, and improves its affinity for organophilicity, so that a close combination is generated between wax powder and silicon dioxide. Organic adsorption and fusion can occur between wax powder and silicon dioxide in any proportion, so that wax powder and silicon dioxide play a synergistic matte effect on the one hand, and the anti-scratch function of wax powder can be simultaneously exerted due to the introduction of a large amount of wax powder in the composite system.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1) The ratio of silica to wax powder can be adjusted according to application requirements to achieve a high proportion of wax powder addition.

[0018] 2) Different from the pore filling of nano-silicon dioxide by high-temperature molten wax, the matte wax powder obtained by the present invention can maintain the high pore volume structure of nano-silicon dioxide, and can maintain or even improve the matte performance of nano-silicon dioxide.

[0019] 3) The composite system with high addition of wax powder can be used not only as a matting agent for the coating, but also as an anti-scratch agent.

[0020] 4) In the traditional coating preparation process, the matting powder settles quickly and will produce hard precipitates after a long storage time. The surface organicization of silicon dioxide and the presence of wax powder in the matting wax powder composite material of the present invention significantly improve the dispersibility and sedimentation problems in the coating, and can extend the shelf stability of the product.

[0021] 5) The present invention regulates the surface properties of silicon dioxide to make it highly organophilic, so that the wax powder and silicon dioxide are tightly bonded; and by adjusting the interface bonding mode, the wax powder and silicon dioxide can play a synergistic role in matting and scratch resistance. Matt wax powder can be used in oily and water-based coatings. When applied on the surface of substrates such as leather, wood, and metal, it can not only obtain excellent matting properties, but also greatly improve the hardness and scratch resistance of the coating surface. The present invention adopts an environmentally friendly method to prepare in a water system, and does not involve organic solvents. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Figure a is the SEM of polyethylene wax. It can be seen from the figure that the polyethylene wax has a highly ordered crystal structure and the particle size is about 4μm. Figure 1Figure b is the SEM of the product of Example 2. It can be seen from the figure that the microstructure of the matte wax powder is an aggregate formed by the accumulation of snowflake-shaped nanoparticles. These nanoparticles are silicon dioxide. The surface polarity of silicon dioxide is adjusted by modification so that it is evenly arranged on the polyethylene surface. Figure 2 Figure a is a picture of the prepared polyurethane left standing for 120 days; it can be seen in the figure that Grace ED2 and the example have been stratified after standing for 120 days; Figure b is the state of the sample being inverted after standing for 120 days, and it can be seen in the figure that Grace ED2 is a hard precipitate and cannot be redispersed evenly, which seriously affects the secondary use. The example is a soft precipitate, which can flow when inverted and can be dispersed evenly with a slight shake, and does not affect the secondary use during the construction process; Figure 3 It is the glossiness seen by the naked eye at different angles; it can be seen from the figure that the blank polyurethane (no matting powder added) coating is bright, while the coating of the embodiment is matte, and there is no obvious change in glossiness when observed from different angles by the naked eye. DETAILED DESCRIPTION

[0023] The following specific embodiments and drawings are used to describe the principles and features of the present invention. The multiple embodiments cited should be understood as explanations of the features of the present invention, and are not intended to limit the scope of the present invention.

[0024] The following examples all use a 2000L stainless steel reactor. In the examples, the process parameters such as drying and pulverization that are not described in detail can be adjusted using conventional techniques in the art.

[0025] Example 1 Add 442.5 kg of sodium carbonate solution with a modulus of 3.36 and a silica content of 25.31% to a 2000 L reactor, add 957.5 kg of pure water, add H2SO4 to a pH of about 7, heat to 80 ° C for 2 hours, and synthesize silica slurry. Add dimethyldiethoxysilane, a silane coupling agent, which accounts for 10% of the solid content of the silica slurry by weight, and stir at 60 ° C for 1 hour and 80 ° C for 2 hours to obtain in-situ modified silica slurry. After the reaction is completed, when the temperature of the in-situ modified silica slurry drops to 60 ° C, add polyethylene wax powder, which accounts for 25% of the solid content of the silica slurry by weight, and stir and emulsify at 60 ° C for 1 hour at a stirring speed of 500 r / min to obtain a mixed suspension; dry the suspension by centrifugal spray to obtain a composite powder; air flow crush the composite powder, and capture it to obtain the product.

[0026] Example 2 Add 242.1 kg of sodium carbonate solution with a modulus of 3.28 and a silica content of 26.02% to a 2000 L reactor, add 1157.9 kg of pure water, add ammonium bicarbonate to a pH of about 7, heat to 60 ° C for 1 hour, and then react at 80 ° C for 1 hour to synthesize silica slurry. Add hexamethyldisilazane accounting for 30% of the solid content of the silica slurry by weight, stir at 60 ° C for 1 hour, and stir at 80 ° C for 2 hours to obtain in-situ modified silica slurry. After the reaction is completed, when the temperature of the in-situ modified silica slurry drops to 40 ° C, add oxidized wax powder accounting for 15% of the solid content of the silica slurry by weight, stir and emulsify at 40 ° C for 1 hour, and the stirring speed is 500 r / min to obtain a mixed suspension; the above suspension is dried by centrifugal spray to obtain a composite powder; the above composite powder is air flow crushed and captured to obtain the product.

[0027] Example 3 410.7 kg of sodium carbonate solution with a modulus of 3.22 and a silica content of 23.86% was added to a 2000 L reactor, 989.3 kg of pure water was added, and hydrochloric acid was added to adjust the pH to 8-9, and the temperature was raised to 80°C for reaction for 2 hours to synthesize silica slurry. Hydroxyl silicone oil accounting for 20% of the solid content in the silica slurry was added thereto, and the mixture was stirred at a constant temperature of 90°C for 3 hours to obtain in-situ modified silica slurry. After the reaction is completed, when the temperature of the in-situ modified silica slurry reaches 40°C, add a low-melting point wax emulsion (Tianjin Kebi Micro Powder Technology Co., Ltd., with a concentration of 35% and a softening point of about 40°C) accounting for 30% of the solid content in the silica slurry by weight, and stir and emulsify at a constant temperature of 40°C for 30 minutes at a stirring speed of 800r / min to obtain a mixed suspension; dry the above suspension by flash evaporation to obtain a composite powder; mechanically crush the above composite powder, and obtain the product after capture.

[0028] Example 4 536.8 kg of sodium carbonate solution with a modulus of 2.96 and a silica content of 23.47% was added to a 2000 L reactor, 863.2 kg of pure water was added, sulfuric acid was added to adjust the pH to 5-6, the temperature was raised to 80 ° C for reaction for 2 hours, and silica slurry was synthesized. Silane coupling agent dimethyldiethoxysilane and 10% γ-aminopropyltriethoxysilane (silane coupling agent KH-550) accounting for 10% of the solid content in the silica slurry were added, and the mixture was stirred at a constant temperature of 80 ° C for 3 hours to obtain in-situ modified silica slurry. After the reaction is completed, when the temperature of the in-situ modified silica slurry drops to 25°C, polyethylene wax powder accounting for 25% of the solid content in the silica slurry by weight is added, and the mixture is stirred and emulsified at a constant temperature of 25°C for 30 minutes at a stirring speed of 1500r / min to obtain a mixed suspension; the suspension is dried by pressure spraying to obtain a composite powder; the composite powder is mechanically crushed and captured to obtain the product.

[0029] Example 5 Add 285.7 kg of sodium carbonate solution with a modulus of 3.23 and a silica content of 24.5% to a 2000 L reactor, add 1114.3 kg of pure water, add ammonium bicarbonate to adjust the pH to 8-9, heat to 60 ° C for reaction for 1 hour, and 80 ° C for reaction for 1 hour to synthesize silica slurry. Add 20% hexamethyldisilazane and 10% silane coupling agent KH-550 by weight accounting for the solid content of the silica slurry, stir at 60 ° C for 1 hour, and stir at 80 ° C for 2 hours to obtain in-situ modified silica slurry. After the reaction is completed, when the temperature of the in-situ modified silica slurry reaches 25°C, add hydrophilic wax powder (Tianjin Kebi Micro Powder Technology Co., Ltd.) accounting for 25% of the solid content in the silica slurry by weight, and stir and emulsify at a constant temperature of 25°C for 30 minutes at a stirring speed of 1500r / min to obtain a mixed suspension; dry the above suspension by pressure spraying to obtain a composite powder; mechanically crush the above composite powder, and obtain the product after capture.

[0030] Comparative Example 1 Compare with Example 1. Add 442.5 kg of sodium carbonate with a modulus of 3.36 and a silica content of 25.31% to a 2000 L reactor, add 957.5 kg of pure water, add H2SO4 to a pH of about 7, heat to 80°C for 2 hours, and synthesize silica slurry. Add dimethyldiethoxysilane, a silane coupling agent, which accounts for 10% of the solid content in the silica slurry, and stir at a constant temperature of 60°C for 1 hour and 80°C for 2 hours to obtain in-situ modified silica slurry, centrifugal spray drying, air flow pulverization, and capture to obtain the product.

[0031] Comparative Example 2 Commercially available high-end fumed silica matting powder Grace ED2.

[0032] Comparative Example 1 is an organically modified silica matting powder, and Comparative Example 2 is a commercially available high-end silica matting powder Grace ED2. No wax powder is added to either of them, and they are compared with the examples.

[0033] The products prepared in the above embodiments and comparative examples were tested for particle size distribution. The obtained matte wax powder and polyurethane were used to prepare matte coatings. For 100g of polyurethane, the addition amount of silica matte powder was 3%, and the addition amount of matte wax powder was calculated based on the silica content of 3%. The glossiness of pure polyurethane without adding matte agent on PU leather was 9.38, and the matt rate was calculated, and the blackness of the coating could be observed by naked eyes. The glossiness of polyurethane without adding matte agent on black and white cardboard was 96.12, and the matt rate was calculated. The obtained matte wax powder and acrylic amino baking varnish were used to prepare matte coatings, and the pencil hardness was tested on tinplate sheets, which could intuitively express the scratch resistance of the coating surface. The results are listed in Table 1.

[0034] Table 1 Application performance of silica / matt wax powder in polyurethane In Table 1, the extinction rates of Examples 1 and 2 are comparable to those of Comparative Example 1, and the extinction rates of Examples 3, 4, and 5 are comparable to those of Comparative Example 2 (Grace ED2), indicating that the addition of wax powder does not affect the extinction efficiency. At the same time, the pencil hardness of the Example (4H) is higher than that of Comparative Example 1 (3H), indicating that the scratch resistance is improved. In addition, the polyurethane prepared in the Example is stored in a ventilated and cool place, and no hard precipitate is formed after standing for 120 days, and it can be evenly dispersed by slight shaking, while the polyurethane prepared by the silica matting powder in the Comparative Example without adding wax powder under the same conditions is a hard precipitate, which cannot be dispersed evenly again without external stirring.

[0035] In summary, in the process of synthesizing modified nano-silica, the present invention compounds wax powder with silica to obtain a matte wax powder. By regulating the surface properties of silica to make it have strong organophilicity, a tight bond is generated between the wax powder and silica; and by adjusting the interface bonding mode, the wax powder and silica can play a synergistic role in matting and scratch resistance. Matt wax powder can be used in oily and water-based coatings. The coating on the surface of substrates such as leather, wood, and metal can not only obtain excellent matte performance, but also greatly improve the hardness and scratch resistance of the coating surface. The present invention adopts an environmentally friendly method to prepare in a water system, and does not involve organic solvents.

[0036] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes that deviate from the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A process for preparing matte wax powder, characterized in that: The following steps are involved: S1: Adjust the pH value of a certain concentration of sodium silicate solution to 3-10, and react at 40-95°C for 0.5-10h to synthesize silica slurry; S2: adding a modifier to the synthesized silica slurry, reacting at 40-95° C. for 1-6 hours to prepare an in-situ modified silica slurry; S3: After the reaction is completed and a certain temperature is reached, wax powder is added to the in-situ modified silica slurry, and the mixture is stirred and emulsified to obtain a silica composite wax powder suspension; S4: drying the suspension to prepare a composite powder; S5: crushing the composite powder to obtain a matte wax powder product.

2. The process for preparing the matte wax powder according to claim 1, characterized in that: The modulus of the sodium silicate solution used in step S1 for synthesizing the silicon dioxide slurry is 2.3-3.6, and the silicon dioxide content is 20-30%.

3. The preparation process of the matte wax powder according to claim 1, characterized in that: Step S1 adjusts the pH by adding one or more of sulfuric acid, hydrochloric acid, nitric acid, citric acid, acetic acid, oxalic acid, sodium bicarbonate, and ammonium bicarbonate.

4. The process for preparing the matte wax powder according to claim 1, characterized in that: The concentration of the silicon dioxide slurry synthesized in step S1 is 4% to 18%.

5. The process for preparing the matte wax powder according to claim 1, characterized in that: The modifier used in step S2 is one or more of a silane coupling agent, a polysiloxane, a cationic surfactant, and a nonionic surfactant, and the amount of the modifier is 3% to 40% of the solid content in the silica slurry.

6. The process for preparing the matte wax powder according to claim 1, characterized in that: The wax powder described in step S3 is one or more of polyethylene wax powder, polypropylene wax powder, polytetrafluoroethylene wax powder, hydrophilic wax powder, oxidized wax powder, and wax emulsion; the amount of wax powder added accounts for 10% to 50% of the solid content mass in the silica slurry described in S2.

7. The process for preparing the matte wax powder according to claim 1, characterized in that: The temperature of step S3 is 20-80°C, and the stirring and emulsifying time is 0.5-4h.

8. The process for preparing the matte wax powder according to claim 1, characterized in that: The drying described in step S4 is one of centrifugal spray drying, pressure spray drying, flash drying and fluidized bed drying, and the pulverizing described in step S5 is mechanical pulverizing or air flow pulverizing.

9. Matt wax powder prepared by the process according to any one of claims 1 to 8.

10. The method for using the matte wax powder according to claim 9, characterized in that: The matte wax powder and polyurethane / polyacrylate are mixed evenly, and a film is coated on a PU leather substrate. After the coating is completed, the film is dried, taken out and cooled to room temperature, and a glossiness test is performed using a multi-angle gloss meter.

Citation Information

Patent Citations

  • Aqueous wax dispersions supported on nano-silica, their preparation methods and applications

    CN103467829B

  • A silica matting agent and its preparation method

    CN111471344B

  • Silica-based matting agents and methods of making and using the same

    CN113382804A